RANCANGAN PENDUKUNG KEPUTUSAN PEMILIHAN TELEVISI BERLANGGANAN MENERAPKAN METODE ANALYTICAL HIERARCHY PROCESS(AHP) - Irfan, Muhammad; Mesran, Mesran; Siregar, Dodi; Suginam, Suginam (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2017)
Television subscription is a product of one of the today's technological developments. Television subscription is a television broadcasting service that is made specifically for viewers who are willing to pay (subscribe) on a regular basis. The number of subscription television products add to the vibrant entertainment business through the glass screen media, before the public only recognize free to air television that can be enjoyed for free. Currently, in some major cities, a number of pay-TV operators compete for customers by offering a variety of exciting television entertainment programs such as news, education, music, movies and so on. This makes it difficult for customers to choose the best television subscription option in providing their services. Implementation of decision support system in the selection of television subscription and using Analytical Hierarchy Process method known as AHP is expected to give the best decision result. Analytical Hierarchy Process is a process of developing a numerical score to streamline alternative decisions based on how each alternative fits the criteria.